ANALISIS PENAMBAHAN SERAT POLYPROPYLENE LIMBAH MASKER MEDIS PADA KINERJA CAMPURAN ASPAL - Riyanto, Sugeng; Qomariah; Asukmajaya R, Bobby (Journal of Civil Engineering, 2023)
Indonesia as a developing country which is now a developed country, has a need for a lot of infrastructure, so it is necessary to have several innovations produced so as to increase the durability and quality of the infrastructure that has been built, one of the infrastructures that is built en masse every year is the highway, of course. When discussing roads, one of the most important components is asphalt, there are various kinds of asphalt used, the durability and strength of asphalt in Indonesia needs to be improved in terms of quality and mixture. Several recent studies in the field of civil engineering have discussed matters relating to the use of waste as a mixed material, thereby converting the discarded material into useful materials for the quality of structures and materials. One of them is plastic, of course there are several plastic materials that can be used as a mixture of concrete and asphalt. The existence of a global pandemic makes everyone obliged to use a mask, masks have a function to filter air that enters the respiratory tract and also help filter air that can remove dirt, viruses or filtered in it, medical masks generally consist of 3 layers of main ingredients, namely cotton on the inside, propylene in the middle and also polyethylene on the outside, medical masks are consumable masks, meaning that after being used for a certain time they must be discarded and replaced with new ones, so that many discarded masks create a new problem, namely mask waste on a large scale, until now the government still has not been able to find out how to use medical masks properly. One part of the medical mask, namely polypropylene, in this study will be used as an additive to asphalt mixtures, which is expected to increase the ability of asphalt to withstand vehicle loads. The results show that asphalt substituted with polypropylene mask waste has a high stability increase, which is an increase of 100% if it is used as a Hotmix. In this study, the final results were obtained, if the asphalt substitution with polypropilene of a mixture of 10% got the most optimal results and in accordance with the 2018 bina marga standards.